Effectiveness of the Representation–Abstraction–Prompt Interpretation (RAP) Strategy in Statistics: A Quasi-Experimental Study among College Students in One State University - Angeline P. Rivad (Advanced Journal of STEM Education, 2026)
This study aimed to determine the effectiveness of Representation-Abstraction-prompt Interpretation (RAP) as a strategy in teaching Statistics among first-year college students. It used a quantitative approach and a quasi-experimental research design. The study's respondents were 50 first-year college students who took Mathematics in the Modern World. They were selected using a matching technique and divided into a comparison group and an experimental group. The research instrument was a standardized multiple-choice test to assess students’ performance and the strategy's effectiveness. The findings revealed significant differences between pre- and post-intervention test scores for both the experimental and comparison groups, indicating that students improved their performance on both the standard and RAP strategies. This implies that students were able to develop their skills in solving problems involving Statistics. Moreover, learners who used the RAP strategy performed better because they were able to transform their basic knowledge into complex ideas by representing, generalizing, and interpreting concepts when learning Statistics. It was observed that students demonstrated their mathematical abilities when they learned through a sequential teaching strategy. Hence, they may engage in more concrete statistical tasks where they can provide meaningful solutions by applying their prior knowledge, representation-abstraction, and prompt interpretation.